1996
DOI: 10.1007/s004670050110
|View full text |Cite
|
Sign up to set email alerts
|

Early age-dependent growth impairment in chronic renal failure

Abstract: We report early linear growth in 73 children (51 boys, 22 girls) with early onset of chronic renal failure (CRF). The inclusion criteria was onset of CRF before 6 months of age, two or more height measurements during the 1st year of life, follow-up for at least 3 years and continuously impaired renal function with a glomerular filtration rate below 50 ml/min per 1.73 m2 at 1 year or later. Only height measurements taken during conservative treatment or dialysis were included. The data were analysed in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Karlberg et al [17] reported that early onset of CRF was associated with an age-dependent growth delay. One-third of the reduction in height occurs during fetal life and one-third during the first postnatal months, probably due to metabolic and/or nutritional impairment.…”
Section: Comparison Of Growth Between Group a And Group Bmentioning
confidence: 98%
“…Karlberg et al [17] reported that early onset of CRF was associated with an age-dependent growth delay. One-third of the reduction in height occurs during fetal life and one-third during the first postnatal months, probably due to metabolic and/or nutritional impairment.…”
Section: Comparison Of Growth Between Group a And Group Bmentioning
confidence: 98%
“…This reduced potential to maximally accelerate growth might be present in children with early-onset chronic renal insufficiency and explain why height retardation of these patients worsens in infancy and puberty, periods of life where growth velocity is normally very high. 2 The phenomenon of catch-up growth was accompanied by expansion of growth cartilage and its hypertrophic zone in rats with normal renal function as well as in rats with CRF. The height of growth cartilage columns is the result of the dynamic equilibrium between two vectors.…”
Section: Discussionmentioning
confidence: 99%
“…The typical growth pattern of a child with congenital CRF whose adult height becomes stunted comprises two periods, infancy and puberty, during which the height deficit worsens, that is, there is a further deviation from the normal percentiles, and the mid-childhood period during which the growth rate parallels the normal growth channel. 2,3 This pattern suggests that the ability to accelerate growth velocity is reduced in individuals with CRF.…”
mentioning
confidence: 99%
“…Malnutrition may be an important contributor to growth impairment in some children, particularly younger children, with CKD [7,9,13,14]. Decreased caloric intake, complicated by an increased incidence of nausea and emesis, is often seen in children with CKD.…”
Section: Malnutritionmentioning
confidence: 98%